Characterization of Aerosol Deposited Cesium Lead Tribromide Perovskite Films on Interdigited ITO Electrodes. (15th January 2021) - These, Albert; Khansur, Neamul H.; Almora, Osbel; Luer, Larry; Matt, Gebhard J.; Eckstein, Udo; Barabash, Anastasia; Osvet, Andres; Webber, Kyle G.; Brabec, Christoph J.
Abstract: Aerosol deposition (AD) is a promising additive manufacturing method to fabricate low‐cost, scalable films at room temperature, but has not been considered for semiconductor processing, so far. The successful preparation of cesium lead tribromide (CsPbBr3 ) perovskite films on interdigitated indium tin oxide (ITO) electrodes by means of AD is reported here. The 20–35 µm thick layers are dense and have good adhesion to the substrate. The orthorhombic Pnma crystal structure of the precursor powder was retained during the deposition process with no signs of defect formation. The formation of electronic defects by photoluminescence spectroscopy is investigated and found slightly increased carrier recombination from defect sites for AD films compared to the powder. A nonuniform defect distribution across the layer, presumably induced by the impact of the semiconducting grains on the hard substrate surface, is revealed. The opto‐electronic properties of AD processed semiconducting films is further tested by electrical measurements and confirmed good semiconducting properties and high responsivity for the films. These results demonstrate that AD processing of metal halide perovskites is possible for opto‐electronic device manufacturing on 3D surfaces. It is believed that this work paves the way for the fabrication of previously unimaginable opto‐electronic devices by additive manufacturing. Abstract : Dense CsPbBr3 films on an indium tin oxide (ITO) electrode are fabricated by the aerosol deposition method (AD). Structural, optical, and electrical characterization reveal good semiconducting properties due to the high defect tolerance of all inorganic perovskite materials. The results demonstrate the high potential of AD‐processing of perovskites for optoelectronic applications.